(untitled) (Fiep Bulletin - online, 2013)
The purpose of this study was to investigate the biomechanical changes (kinematics and articulate the level of maximum activity (root mean square-RMS)) and physiological (lactate) of the muscles involved in the exercise series in bench press intervals for trained individuals. The experimental group was composed of five volunteers (26.2 ± 5.6 years; 77.54 ± 9.56 kg, 168.1 ± 4.20 cm), all trained with more than two years of experience with the movement studied. As a criterion for inclusion, they could not show any injury myo-osteo-articular in the upper limb. The electromyographic signal was acquired through the equipment EMG 1000 (Lynx Inc.), composed of an amplifier, 8 channel power (with four auxiliary channels) for pre-electrodes liabilities. The assessment cinematic markers used spherical styrofoam (2.5 cm diameter) covered with reflective tape placed on anatomical points of the upper limbs. These data were obtained through a video camera, 30 HZ (SONY ®, Sao Paulo, Sao Paulo, Brazil), and subsequently analyzed in the Vicon Motion Analysis System (Vicon Corporation, Los Angeles, CA. USA). For the collection of blood lactate, there were punctures in the distal part of the index finger of right hand with the unit Accu-Chek ® softclix ®. After the punch, the droplets of blood were placed on the tapes WB lactate Cobas ® and inserted into lactimeter Accutrend ® for consideration. The analysis of variance showed no significant difference when comparing the results submitted to the displacement articulate and electromyographic analysis of the behavior, but compared to the levels of blood lactate there were significant variations between the measures collected, especially when compared all series in relation to rest, as well as for the second and third rounds on the first, getting no significant differences between the second and third series of exercises.